Green Finance Revolution: Investigating the Role of Sustainable Investments in Driving Corporate Profitability in Indonesia - Afandy, Chairil (International Journal of Business, Law, and Education, 2024)
This study investigates the role of sustainable investments in driving corporate profitability in Indonesia, with a particular focus on the mediating role of ESG (Environmental, Social, and Governance) performance and the moderating effect of regulatory frameworks. Using data from 210 companies across various sectors, the study employs structural equation modeling (SEM) to test the proposed relationships. The results show that sustainable investments significantly enhance corporate profitability, with ESG performance acting as a key mediator in this relationship. Additionally, regulatory frameworks are found to moderate the impact of sustainable investments on profitability, amplifying the positive effects when regulatory support is strong. These findings underscore the importance of integrating sustainability into business strategies and highlight the crucial role of supportive policies in fostering green investments. The study contributes to the growing literature on green finance by providing empirical evidence on the financial benefits of sustainability in emerging markets like Indonesia.